Arsitektur Tropis Sebagai Pendekatan Redesain Perpustakaan Dan Kearsipan Kabupaten Indragiri Hilir - Zurnalis, Zurnalis; Firzal, Yohannes; S, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Library redesign and archive of Indragiri Hilir has vision to make the offices and the archives professionally, foremost in information service and concern about learning scoiety in Indragiri Hilir. It migh not happen without facilites which support for this situation, because nowadays is really apprehensive. It became a reason why redesign is needed, to build appropriate building and to get vision of library and archive of Indragiri Hilir. In redesign planning of library and archive of Indragiri Hilir, applying of panning approach was tropical architecture principle. Some of principles that used in this planning were orientation project, sun screen, cross ventilation and vegetation. In addition, this planning took attractive characteristics concept psychologically. From this concept, the writer develop the application of architectural character for the building. From the tropical architecture approach and attractive concept, it becomes writer’s foundation in library and arcvive redesign panning of Indragiri Hilir.Key words: Redeain, Library and Archive, Tropical Architecture, Attractive